Ssociation Of Between Duration Of Computer Light Exposure And Computer Vision Syndrome Incidences In Employees Who Are Using Computers - Danuseputro, Kevin A; Kurniawati, Nita; Warsanto, J Alphonsus (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
ntroduction: The use of computers is increasing these days. The use of computer causeserious eye complaints in the form of Computer vision syndrome (CVS) symptoms. CVS is adisease associated with symptoms of watery eyes, blurred vision, eye redness, eye strain, etc.Consequences of these symptoms can reduce working productivity or efficiency. Allegedlyone of the factors that trigger CVS symptoms is the duration of computer’s light exposure. Purpose: To determined whether there is association between duration of computer lightexposure with Computer Vision Syndrome (CVS)’s incidence in employees who usecomputers. Method: This study was an observational analytic study with cross-sectional design. Thesampling method used was purposive sampling. The total sample in this study was 85 people.The duration of light exposure was measured by interview while the CVS was measuredusing the CVS-q questionnaire. Data analysis was performed using the SPSS program withchi-square test. Results:The results of this study found that people who work more than 4 hours were morelikely to experienced symptoms of CVS compared to people who work less than 4 hours. Theresults showed that there was a significant association between the duration of computer lightexposure with computer vision syndrome (CVS) incidences in employees who are usingcomputers. Conclusion: There was an association between the duration of computer light exposure withcomputer vision syndrome (CVS) incidences in employees that using computers